2019
DOI: 10.4314/nvj.v40i3.8
|View full text |Cite
|
Sign up to set email alerts
|

Participatory epidemiological survey of foot-and-mouth disease among some cattle diseases in some pastoral communities of Niger, north central, Nigeria

Abstract: Foot-and-mouth disease (FMD) is known to cause significant financial losses, making it a threat to the livelihood and food security. Disease surveillance in pastoral areas are often difficult because human populations are relatively small and highly mobile, and requires considerable flexibility and commitment. Participatory epidemiological approach was used to assess relative burden, seasonality and perceived risk factors of FMD among other important cattle diseases in cattle population of pastoral communities… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 17 publications
1
0
0
Order By: Relevance
“…This implies that Contagious Bovine Pleuropneumonia (Bunsude) and blackleg (Suharu) were the most prevalent cattle disease in the study area due to their constant occurance which affects the performance or causes death of the cattle which could necessitate pastoralist to know the period and the prevalent nature of the diseases in among herds. The results is in correspondence to the findings of Niamir-Fuller (2016), Jonesa et al (2019), Wungak et al (2019) who reported that Contagious bovine pleuropneumonia (CBPP), Foot and mouth diseases and Trypanosomiasis diseases were some major prevalent cattle diseases common in pastoralism.…”
Section: Results and Discussion Prevalence Of Cattle Diseasessupporting
confidence: 90%
“…This implies that Contagious Bovine Pleuropneumonia (Bunsude) and blackleg (Suharu) were the most prevalent cattle disease in the study area due to their constant occurance which affects the performance or causes death of the cattle which could necessitate pastoralist to know the period and the prevalent nature of the diseases in among herds. The results is in correspondence to the findings of Niamir-Fuller (2016), Jonesa et al (2019), Wungak et al (2019) who reported that Contagious bovine pleuropneumonia (CBPP), Foot and mouth diseases and Trypanosomiasis diseases were some major prevalent cattle diseases common in pastoralism.…”
Section: Results and Discussion Prevalence Of Cattle Diseasessupporting
confidence: 90%